The impact of leadership on employee well-being: on-site compared to working from home - Daniel Lundqvist; Cathrine Reineholm; Christian Ståhl; Andreas Wallo (BMC, 2022)
Abstract Background The Covid-19 pandemic has brought significant changes to the way people work and there are several reasons to believe that working from home will become more common in the future. Yet more knowledge is needed on whether the effectiveness of leadership differs if the work is performed remotely compared to on-site work. Purpose The aim of this study is to examine the place of work as a moderator for the effectiveness of leadership on employee well-being. Method A survey was answered by 364 white-collar workers, employed by a larger Swedish municipality, who because of the covid-19-pandemic were offered to work from home. Results The employees working in their regular office perceived having more sufficient work equipment. No other differences were found in the investigated variables. Supportive leadership was associated with all investigated well-being variables in the hypothesised directions. Place of work did not moderate the relationship between Support leadership and the investigated well-being outcomes (Job satisfaction, Stress, General well-being). Conclusion This study shows that there are few differences between employees working from home or working on-site during the Covid-19 pandemic. The supportive leadership of the closest manager seem to be important for well-being regardless of the worksite.